Validity and reliability of intraoral conventional tracer and intraoral digital tracer in different positions for recording horizontal jaw relation in edentulous patients - Nikhil Bharat Abbad; Rajeev Srivastava; Vivek Choukse; Vandana Sharma (Wolters Kluwer Medknow Publications, 2019)
Aim: The purpose of the study is to evaluate and compare the horizontal mandibular positions recorded between intraoral conventional tracer and intraoral digital tracer in upright and supine position. Materials and Methods: Twenty-four edentulous patients with well-formed ridge and adequate interarch distance space were selected. MATLAB software was assimilated with intraoral digital tracer and was utilized in the study for recording the horizontal movements of the mandible, i.e., gothic arch tracing by intraoral digital tracer and was observed on a laptop with the help of MATLAB Software. For each subject, multiple mandibular readings were recorded and analyzed through software, and similar readings were recorded with conventional intraoral tracers. The comparison between intraoral conventional tracer and intraoral digital tracer was done to assess the reliability. Moreover, the consistency of recording horizontal mandibular position was also compared between upright and supine position. Results: The data were procured and utilized in comparison for different positions revealed statistically significant difference by using Student's Paired t-test. The test resulted in supine position better compared to upright position (P = 0.0001). The association between supine position with upright position was calculated using Fischer's exact test, and it was also found to be statistically significant (P = 0.002). The Pearson's Correlation analysis was performed to check the agreement between upright and supine position and very weak downhill correlation (r2= −0.130) was observed between the two variables. Conclusion: On evaluation and comparison of horizontal mandibular position, it was found that the intraoral digital tracing technique is more valid compared to conventional intraoral tracer technique. It was also observed that the consistency of reproducibility in recording horizontal mandibular position in supine position is significantly higher than upright position.